Documentary Films in India - Sharma, Aparna. author. aut Link
XIII, 276 p.
Keywords: This book introduces the diverse practices of three non-canonical practitioners: David MacDougall, Desire Machine Collective and Kumar Shahani. It offers analysis of their documentary methods and aesthetics, exploring how their oeuvres constitute a critical and self-reflexive approach to documentary-making in India.